Possible roles of sestrin2 in multiple sclerosis and its relationships with clinical outcomes - ODABAS, Faruk Omer; UCA, Ali Ulvi; AKDAG, Turan; DEMİRDÖGEN, Filiz; ALTAS, Mustafa; TOKGOZ, Osman Serhat (Arquivos de Neuro-Psiquiatria, 2022)
Background: Characterized by demyelination, inflammation and axonal damage, multiple sclerosis (MS) is one of the most common disorders of central nervous system led by the immune system. There is an urgent and obvious need for biomarkers for the diagnosis and follow-up of MS. Objective: To investigate serum levels of sestrin2 (SESN2), a protein that responds to acute stress, in MS patients. Methods: A total of 85 participants, 40 patients diagnosed previously with relapsing-remitting MS and 45 healthy controls, were included. Serum SESN2 parameters were investigated in blood samples drawn from each participant in the patient and control groups. Results: SESN2 levels were significantly lower in MS patients than in controls (z: -3.06; p=0.002). In the ROC analysis of SESN2, the predictive level for MS was 2.36 ng/mL [sensitivity, 72.50%; specificity, 55.56%; p=0.002; area under the curve (AUC)=0.693]. For the cut-off value in both groups, SESN2 was an independent predictor for MS [Exp (B)=3.977, 95% confidence interval (95%CI) 1.507-10.494 and p=0.013]. Conclusions: The decreased expression of SESN2 may play a role in MS pathogenesis, and SESN2 could be used as a biomarker for MS and as immunotherapeutic agent to treat MS.
Keywords: Multiple Sclerosis; Sestrins; Apoptosis; Biomarkers; Inflammation; Oxidative Stress